Modeling of the Acoustic Properties of Foamed Polypropylene Panels - Patrycja ŚWIRK; Lucyna LENIOWSKA (Engineering Transactions, 2025)
This article presents research on modelling baffles with the desired properties of the sound absorption coefficient (SAC). The purpose of the study was to model and compare the SAC values based on selected theoretical models with the results obtained from measurements of this coefficient in panels made of foamed polypropylene. The assessment of sound absorption properties was carried out using two theoretical models: the Johnson–Champoux–Allard (JCA) model and the Sgard model. The accuracy of the calculated SAC was verified based on laboratory measurements of this parameter for selected material configurations, using the technique of two microphones in an impedance tube. Both theoretical and experimental studies were conducted on porous materials in the form of granules. The application of the Sgard model yielded the best results, with the smallest discrepancies in relation to the experimental tests. The results can be used to improve the SAC and efficiency of acoustic panels whose basic material is foamed polypropylene.